Physical Fitness Profile of Malang Phase B Students for Pre Service Physical Education Teachers - M. Alfian Jauhar Munawar; Muhammad Alfan (Universitas Negeri Semarang, 2026)
Physical Education, Sport, and Health (PJOK) is an important component in supporting students’ physical development, motor skills, and readiness to learn. However,the increasing sedentary behavior among urban children may reduce their physical fitness levels. This study aimed to identify the physical fitness profile of Phase B students in Malang City as a foundation for preparing PJOK learning plans for pre-service teachers. The research used a quantitative approach with a descriptive design and a test-based survey method. It was conducted at SDN Percobaan 1 Malang, with students selected through purposive sampling. The instrument used was the Indonesian Student Fitness Test (TKSI) for Phase B. The data were analyzed using descriptive statistics, including frequencies and percentages.The results showed that students’ physical fitness was mostly in the good category (44.29%), followed by moderate (25.71%), very good (17.86%), and poor (12.14%). Different achievements were found in each test component. Hand-eye coordination and agility obtained better results than flexibility and core muscle endurance. These findings indicate that students’physical activity tends to develop coordinative and dynamic movement skills more than flexibility and muscular strength. Therefore, TKSI results can be used as a basis for designing PJOK learning that is more relevant, adaptive, and aligned with students’needs.